Using preimplantation genetic testing for monogenic disease for preventing citrullinemia type 1 transmission - Wu, Zubo; Liang, Tao; Liu, Yi; Ding, Xiaofang; Shu, Defeng (Frontiers in Genetics, 2024)
The aim of this study is to investigate if Preimplantation Genetic Testing (PGT) can effectively identify unreported variants according to American College of Medical Genetics and Genomics (ACMG)to prevent citrullinemia type 1 affection.This study involves a detailed case analysis of a family with history of citrullinemia type 1, focusing on the use of PGT for monogenic diseases (PGT-M). The genetic variants were identified using ACMG guidelines, and PGT was employed to prevent the inheritance of these variants. The study included haplotype analysis and Sanger sequencing to confirm the results.The study identified previously unreported variations in the ASS1 gene causing citrullinemia type 1. PGT successfully prevented the transmission of these variants, resulting in the birth of a healthy fetus. However, challenges such as allele dropout (ADO) and gene recombination were encountered during haplotype analysis, which could potentially defeat the diagnosis. The study demonstrated that combining haplotype analysis with Sanger sequencing can enhance the accuracy of PGT.Preimplantation Genetic Testing (PGT) targeting likely pathogenic and pathogenic variants in the ASS1 gene, as rated by ACMG, allows the birth of healthy infants free from citrullinemia type 1. Additionally, the establishment of single haplotypes and Sanger sequencing can reduce the misdiagnosis rate caused by allele dropout (ADO) and genetic recombination.